Perceived quality of health care in a public network of the municipality of Pasto in Colombia - Yépez-Chamorro, María Clara; Ricaurte-Cepeda, Melissa; Jurado, Daniel Marcelo (Universidad y Salud, 2018)
Introduction: Perceptions of users from the health services are indispensable indicators for quality on the processes of health care. Objective: To know the perceptions of the users of a public network of the municipality of Pasto, Colombia versus the quality of health services at the first level of attention. Materials and methods: A qualitative research with a hermeneutic historical approach was conducted with 28 participants, who were users of rural and urban centers of care. The techniques developed for collecting the information were semi-structured interviews and a focal group. The research process addressed five dimensions: trust, reliability, responsibility, responsiveness and tangibility. Results: In the dimensions mentioned before, the difficulties of access by administrative and geographical aspects, problems in the opportunity in the specialized attention, faults in the reference and counter-reference and the necessity of infrastructure improvements in the IPS were identified as limitations in the quality. Moreover, it was recognized that the good treatment of the healthcare personnel is an aspect that affects in a positive way in the perception of the quality. Conclusions: Improving the quality of health services, requires recognizing users as the center of attention, with a view to the integrality, continuity, efficiency, efficiency and fairness of services, under the fundamental principle of guarantee and protection of the right to health and life worthy of patients.